The Effect of Addition of Garlic and Lemongrass on Media for the Preparation of Salted Chicken Eggs on Organoleptic Test - Diah Reni Asih; Rohmatul Anwar (Animal Husbandry Study Program, Faculty of Agriculture, Timor University, 2023)
The objective of this research was to observe organoleptic quality of salted egg with garlic and lemongrass addition. The materials used in this study were 40 eggs, water, garlic, lemongrass and krasak salt (table salt). This study used a completely randomized design (CRD) with 3 treatments and 3 replications, namely P0 = Control, P1 = Addition of garlic and lemongrass 15%, and P2 = Addition of garlic and lemongrass 30%. The parameters observed this study were the organoleptic values ​​of color, taste and texture. Data were analyzed using ANOVA, if significantly different then continued with Duncan's test. The results of the study adding garlic and lemongrass had a significant effect on organoleptic values ​​(taste and texture). The average value of the organoleptic test for salted chicken eggs is color 4.3-4.53; taste 3.93-4.83 and texture 3.40-4.43. Based on these results it can be concluded that the best results on organoleptic values ​​(color, taste and texture) are P2 (30%). It is suggested to further researchers to conduct further research to find out the shelf life of salted eggs for commercialization in the community.